Parapet structure from special shaped TRC blocks - Jiří Pazderka; Petr Hájek; Michal Nývlt; Hana Žáková (Acta Polytechnica CTU Proceedings, 2022)
The paper describes innovative parapet solution based on special shaped blocks made form textile-reinforced concrete - TRC. The blocks are designed for a placement at the parapet of building with a flat roof. The solution is appropriate for buildings with precast-concrete bearing structure by following the principle of precast technology (short construction time, minimal technological pauses). However, presented parapet TRC blocks can be used for energy efficient buildings as well in combination with thick layers of thermal insulation. The technical solution was registered as utility model no. CZ27642(U1).